The influence of nonrandom mating on population growth. - Schindler, S; Neuhaus, P; Gaillard, J; Coulson, T (University of Chicago Press, 2013)
When nonrandom mating alters offspring numbers or the distribution of offspring phenotypes, it has the potential to impact the population growth rate. Similarly, sex-specific demographic parameters that influence the availability of mating partners can leave a signature on the population growth rate. We develop a general framework to explore how mating patterns and sex differences influence the population growth rate. We do this by constructing a two-sex integral projection model to explore ways in which altering the mating behavior from random to nonrandom mating (assortative, disassortative, or selection for size) and altering demographic parameters in one or both sexes (growth, survival, and parental contribution to offspring phenotype) affect the population growth rate. We demonstrate our framework using data from a population of Columbian ground squirrels. Our results suggest that the population growth rate is substantially affected when nonrandom mating is linked to sex differences in demographic parameters or parental contributions to offspring phenotype, but interestingly, the effect of the mating pattern alone is rather small. Our results also suggest that the population growth rate of Columbian ground squirrels would increase with the degree of disassortative mating and with the degree of the mating advantage of large individuals.